Penggunaan Podcast Sebagai Media Pembelajaran Sastra Indonesia - Muhamad Farhan (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2022)
This study discusses how podcasts are used as a medium for learning Indonesian literature. The purpose of this study is to find out how to use podcasts as a medium for learning Indonesian literature in universities. The subjects of this study were active students of Indonesian Language and Literature Education at UIN Syarif Hidayatullah, all of whom were ready to become research respondents. The method used in this study is a qualitative descriptive method. The data source of this research is a questionnaire on the use of podcasts as a medium for learning literature which is distributed online via google form. The data are in the form of percentages and respondents' answers to multiple choice questions and short essays on the use of podcast media in learning literature. The method of data analysis is done by grouping the average score of answers on the questionnaire, looking for the percentage of respondents' responses, and interpreting the results of respondents' responses based on percentages. The result of this study is that the use of podcasts as a medium for learning Indonesian literature has been carried out more or less. Respondents who are students in learning literature feel that podcasts as a medium for learning literature are quite effective, because they are easily accessible, can be played repeatedly, are fun, and add variety to learning.